2019
DOI: 10.4312/ala.9.1.29-57
|View full text |Cite
|
Sign up to set email alerts
|

The Integration Functions of Topic Chains in Chinese Discourse

Abstract: The topic chain, one of the essential organization devices in Chinese discourse, is highlighted by the use of many co-referential zero forms. Although the topic chain has been realized to play an important role in organizing discourse, few attempts have been made to explore how the topic chain forms an integrated and meaningful unit and facilitates discourse organization, which are called the “integration functions” of the topic chain in this paper. This study, based on a comprehensive review of topic chain st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The first type of semantic shift hypothesized to affect meaning completeness judgment is "topic shift". In Chinese, a block of clauses may form a "topic chain" when they share the same topic, which is explicitly mentioned in a topic clause but implicitly referred to with an empty category in several comment clauses (Li, 2004;Sun, 2019), as illustrated in the third sentence in Example (1), in which the topic "Cuicui" is explicitly mentioned in clause (e) and stays the same through the end of the topic chain. A "topic shift" occurs if a different topic arises in the next block of clauses.…”
Section: Research Questions and Hypothesismentioning
confidence: 99%
“…The first type of semantic shift hypothesized to affect meaning completeness judgment is "topic shift". In Chinese, a block of clauses may form a "topic chain" when they share the same topic, which is explicitly mentioned in a topic clause but implicitly referred to with an empty category in several comment clauses (Li, 2004;Sun, 2019), as illustrated in the third sentence in Example (1), in which the topic "Cuicui" is explicitly mentioned in clause (e) and stays the same through the end of the topic chain. A "topic shift" occurs if a different topic arises in the next block of clauses.…”
Section: Research Questions and Hypothesismentioning
confidence: 99%
“…The multiclausal aspect of Topic Chains supports Figure 2: Analysis steps adopted in this study: (a) Grammatical subjects and objects of each main verb are identified via dependency parsing on the whole story discourse of The Little Prince (See a sentence example from Table 1, columns "S", "V", "O"); (b) Semantic role annotation: for all the subjects and objects, annotate their semantic roles as AGENT or PATIENT (See Table 1 column "V-agent" and "Vpatient"); (c) Character role annotation: assign story character roles to the entities, see character occurrences in Table A1, and Table 1 column "character"; (d) History verb retrieval for each story character: for each story character, tabulate the verbs that are its main verbs being used in the discourse (See example Table A3); (e) Relevance between history verbs and a current verb: for each current verb, calculate its relevance to the history verbs, and sum with or without their distance weight (See Table 2 and A5); (f) Salience of the correct character: for each verb, calculate how "salient" the correct character is compared to all other characters (See example Table A6); (g) Group test between pro-drop verbs vs. non-pro-drop verbs, and apply logistic regression to test predictability of character salience on dropping behavior (See group results in Table 3 and Figure 3). long-distance coreference (Sun, 2019). Taking a dynamic perspective, Pu (2019b) suggests that a topic chain "encodes a referent that is cognitively most accessible at the moment of discourse production, as enhanced by maximum discourse coherence of topic continuity and thematic coherence".…”
Section: Related Workmentioning
confidence: 99%
“…Every zero form from C1-C9, however, has the same constituent, "yellow flower wheat fruit", and this same constituent occurs in each clause. (Sun 2015(Sun , 2018(Sun , 2019a(Sun , 2019b Some ZAs in this passage have nominal referents derived from the previous clauses through gradual accumulation, but sometimes their antecedents are not always nominal, for example, the…”
Section: Gradual Accumulation Of Referentmentioning
confidence: 99%